An Efficient Method for the RCS Reduction of Cavities in the Ground Plane (Advances in Applied Mathematics and Mechanics, 2024)
This paper investigates the reduction of backscatter radar cross section (RCS)for cavities embedded in the ground plane. It is established by placing a multilayeredradar absorbing material (RAM) at the bottom of the cavities. The minimization of thebackscatter RCS is formulated as a bound constrained optimization problem. A newvertical mode expansion method is developed to solve the scattering problem, andit is integrated into the gradient projection method to obtain the optimal compositecoating. Numerical examples show that the method we developed is efficient and thebackscatter RCS can be significantly reduced.